Motherhood in the Time of Coronavirus: The Impact of the Pandemic Emergency on Expectant and Postpartum Women’s Psychological Well-Being - Molgora, Sara; Accordini, Monica (Frontiers in Psychology, 2020)
The birth of a child is a critical and potentially stressful experience for women, entailing several changes both at the individual and interpersonal level. This event can lead to different forms of distress, ranging in intensity and duration. Many studies highlighted medical, psychological, and social variables as risk factors potentially influencing the onset or aggravation of perinatal maternal conditions. The current pandemic emergency and the restrictive measures adopted by local governments to prevent the spread of the coronavirus infection may negatively affect mothers-to-be and new mothers potentially increasing the likelihood of anxiety, depressive or post-traumatic symptoms to develop. Moreover, the forced quarantine combined with the limited access to professional or family support may increase feelings of fatigue and isolation. The present study aims to investigate women’s psychological well-being during pregnancy and in the first months after childbirth, integrating the evaluation of some traditionally studied variables with the specificities of the current situation. 575 Italian women have been administered an online self-report questionnaire assessing the presence of anxiety disorders, depressive and post-traumatic symptoms as well as the expectations toward childbirth (for mothers-to-be) or the subjective experience of childbirth (for postpartum women). Findings revealed a higher percentage of women than that reported in the literature scored above the clinical cut-off both during pregnancy and postpartum on a series of measures of psychological well-being, thus demonstrating that this period was perceived as particularly challenging and stressful and had significant impact on the women’s well-being. Moreover, some socio-demographic, medical, and pandemic-related variables, especially the lack of presence and support from one’s partner during labor and delivery as well as in the first days postpartum was found to predict women’s mental health. These findings suggest the need for developing specific interventions targeted at women who cannot benefit from the support of their partners or family.